mathlib documentation

algebra.geom_sum

def geom_series {α : Type u} [semiring α] :
α → → α

Sum of the finite geometric series $\sum_{i=0}^{n-1} x^i$.

Equations
theorem geom_series_def {α : Type u} [semiring α] (x : α) (n : ) :
geom_series x n = ∑ (i : ) in finset.range n, x ^ i

@[simp]
theorem geom_series_zero {α : Type u} [semiring α] (x : α) :

@[simp]
theorem geom_series_one {α : Type u} [semiring α] (x : α) :

@[simp]
theorem op_geom_series {α : Type u} [ring α] (x : α) (n : ) :

def geom_series₂ {α : Type u} [semiring α] :
α → α → → α

Sum of the finite geometric series $\sum_{i=0}^{n-1} x^i y^{n-1-i}$.

Equations
theorem geom_series₂_def {α : Type u} [semiring α] (x y : α) (n : ) :
geom_series₂ x y n = ∑ (i : ) in finset.range n, (x ^ i) * y ^ (n - 1 - i)

@[simp]
theorem geom_series₂_zero {α : Type u} [semiring α] (x y : α) :

@[simp]
theorem geom_series₂_one {α : Type u} [semiring α] (x y : α) :

@[simp]
theorem geom_series₂_with_one {α : Type u} [semiring α] (x : α) (n : ) :

theorem commute.geom_sum₂_mul_add {α : Type u} [semiring α] {x y : α} (h : commute x y) (n : ) :
(geom_series₂ (x + y) y n) * x + y ^ n = (x + y) ^ n

$x^n-y^n = (x-y) \sum x^ky^{n-1-k}$ reformulated without - signs.

theorem geom_series₂_self {α : Type u_1} [comm_ring α] (x : α) (n : ) :
geom_series₂ x x n = (n) * x ^ (n - 1)

theorem geom_sum₂_mul_add {α : Type u} [comm_semiring α] (x y : α) (n : ) :
(geom_series₂ (x + y) y n) * x + y ^ n = (x + y) ^ n

$x^n-y^n = (x-y) \sum x^ky^{n-1-k}$ reformulated without - signs.

theorem geom_sum_mul_add {α : Type u} [semiring α] (x : α) (n : ) :
(geom_series (x + 1) n) * x + 1 = (x + 1) ^ n

theorem geom_sum₂_mul_comm {α : Type u} [ring α] {x y : α} (h : commute x y) (n : ) :
(geom_series₂ x y n) * (x - y) = x ^ n - y ^ n

theorem geom_sum₂_mul {α : Type u} [comm_ring α] (x y : α) (n : ) :
(geom_series₂ x y n) * (x - y) = x ^ n - y ^ n

theorem geom_sum_mul {α : Type u} [ring α] (x : α) (n : ) :
(geom_series x n) * (x - 1) = x ^ n - 1

theorem mul_geom_sum {α : Type u} [ring α] (x : α) (n : ) :
(x - 1) * geom_series x n = x ^ n - 1

theorem geom_sum_mul_neg {α : Type u} [ring α] (x : α) (n : ) :
(geom_series x n) * (1 - x) = 1 - x ^ n

theorem mul_neg_geom_sum {α : Type u} [ring α] (x : α) (n : ) :
(1 - x) * geom_series x n = 1 - x ^ n

theorem geom_sum {α : Type u} [division_ring α] {x : α} (h : x 1) (n : ) :
geom_series x n = (x ^ n - 1) / (x - 1)

theorem geom_sum_Ico_mul {α : Type u} [ring α] (x : α) {m n : } :
m n(∑ (i : ) in finset.Ico m n, x ^ i) * (x - 1) = x ^ n - x ^ m

theorem geom_sum_Ico_mul_neg {α : Type u} [ring α] (x : α) {m n : } :
m n(∑ (i : ) in finset.Ico m n, x ^ i) * (1 - x) = x ^ m - x ^ n

theorem geom_sum_Ico {α : Type u} [division_ring α] {x : α} (hx : x 1) {m n : } :
m n∑ (i : ) in finset.Ico m n, x ^ i = (x ^ n - x ^ m) / (x - 1)

theorem geom_sum_inv {α : Type u} [division_ring α] {x : α} (hx1 : x 1) (hx0 : x 0) (n : ) :
geom_series x⁻¹ n = (x - 1)⁻¹ * (x - (x⁻¹ ^ n) * x)

theorem ring_hom.map_geom_series {α : Type u} {β : Type u_1} [semiring α] [semiring β] (x : α) (n : ) (f : α →+* β) :

theorem ring_hom.map_geom_series₂ {α : Type u} {β : Type u_1} [semiring α] [semiring β] (x y : α) (n : ) (f : α →+* β) :
f (geom_series₂ x y n) = geom_series₂ (f x) (f y) n